2022
DOI: 10.3389/fnut.2022.804046
|View full text |Cite|
|
Sign up to set email alerts
|

Health Benefits of Probiotics in Sport and Exercise - Non-existent or a Matter of Heterogeneity? A Systematic Review

Abstract: BackgroundThe use of probiotics in sports has been growing in recent years, as up to 50% of athletes suffer from training- and performance-limiting gastrointestinal (GI) problems. Moreover, repeated exhaustive exercise and high training loads may lead to a transiently depressed immune function, associated with an increased risk of upper respiratory tract infection (URTI).AimTo provide a qualitative analysis of probiotic effects on URTI, GI symptoms and the immune system in healthy individuals under considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…However, an active debate has been going on for years about whether the consumption of probiotics is beneficial for nonpatients in quality-of-life improvement and disease prevention ( 27 29 ). Although previous studies supported a beneficial effect of probiotics in enhancing immunity against the common cold, which can reduce the incidence ( 30 ), duration ( 31 ), and symptoms ( 32 ) of the common cold ( 28 , 33 , 34 ), some reported that the effects of the probiotics on the immune system and gastrointestinal symptoms in nonpatients are limited ( 29 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an active debate has been going on for years about whether the consumption of probiotics is beneficial for nonpatients in quality-of-life improvement and disease prevention ( 27 29 ). Although previous studies supported a beneficial effect of probiotics in enhancing immunity against the common cold, which can reduce the incidence ( 30 ), duration ( 31 ), and symptoms ( 32 ) of the common cold ( 28 , 33 , 34 ), some reported that the effects of the probiotics on the immune system and gastrointestinal symptoms in nonpatients are limited ( 29 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, an active debate has been going on for years about whether the consumption of probiotics is beneficial for nonpatients in quality-of-life improvement and disease prevention ( 27 29 ). Although previous studies supported a beneficial effect of probiotics in enhancing immunity against the common cold, which can reduce the incidence ( 30 ), duration ( 31 ), and symptoms ( 32 ) of the common cold ( 28 , 33 , 34 ), some reported that the effects of the probiotics on the immune system and gastrointestinal symptoms in nonpatients are limited ( 29 , 35 ). One approach by which probiotics impact the host immune system is through the microbial metabolism that arises from intestinal microbiota catabolism ( 36 39 ): e.g., functional metagenomic studies have identified the associations between host proinflammatory cytokines and microbial tryptophan and palmitoleic acid metabolic pathways ( 37 , 38 , 40 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…These benefits included the impact of probiotics on oxidative stress, inflammatory response, sports performance, immune-system function, and upper respiratory tract infection (URTI) [28]. An imbalance in gut microbiota may limit the training performance of athletes, leading to poor competitiveness, a decline in overall well-being, fatigue [29], depression, and anxiety [30]. Therefore, problems with a high prevalence of upper respiratory (URTI) and gastrointestinal (GI) tract infections are welldocumented and pertain to increased permeability of the gastro-intestinal epithelial wall, mucous thickness disruption, and subsequent higher rates of bacterial translocation [31].…”
Section: Selectivity For Growth Of Probiotic Strains and Prebioticmentioning
confidence: 99%
“…As the blood supply to the GI tract decreases by 60 to 70% at exercise intensities of 70% of maximum oxygen consumption (VO2max), this decrease in blood supply may also reduce mesenteric blood flow [30]. Increasing evidence supports the idea that maintaining a healthy balance of beneficial bacteria in the microbiome can support immunity, leading to fewer illnesses and sustaining optimal health.…”
Section: Selectivity For Growth Of Probiotic Strains and Prebioticmentioning
confidence: 99%
“…Recently published narrative or opinion piece reviews exploring prebiotics (i.e., non-digestible material that can be fermented by bacteria in the lower gastrointestinal tract), probiotics (i.e., live bacteria which survive transit to colonize the lower gastrointestinal tract), and synbiotics (a combination of pre-and pro-biotics) in active adults, have implied a beneficial effect on the gastrointestinal tract in response to exercise and improved performance; however the primary focus has been on exercise performance or immunological outcomes (22)(23)(24)(25)(26)(27)(28)(29). Unlike these narrative or opinion-based reviews, recent systematic literature reviews (SLR) that focused and/or included pro-and/or synbiotic supplementation, concluded inconsistent methodologies and/or findings that provided no convincing evidence of any substantial beneficial effects resulting from probiotic supplementation in healthy populations (30)(31)(32). Although it is important to note that these SLR did not comprehensively evaluate EIGS markers or changes to fecal bacterial taxa or SCFA.…”
Section: Introductionmentioning
confidence: 99%